Protective Effect of Recombinant Proteins of Cronobacter Sakazakii During Pregnancy on the Offspring - Song, Jia-rong; Fu, Yan-wen; Li, Ping; Du, Ting; Du, Xin-jun; Wang, Shuo (Frontiers in Cellular and Infection Microbiology, 2020)
Cronobacter sakazakii is a food-borne pathogen carried in milk powder that can cause severe bacteremia, enterocolitis and meningitis in newborns, which can lead to death of newborns. Preventing infection by this pathogen is significant to the health of newborns. Since infants and young children are the main target group of C. sakazakii, it is considered that maternal immunity can enhance the protection of newborns. Previous studies showed that two proteins of C. sakazakii (GroEL and OmpX) exhibited high expression levels and elicited strong immune reactions, suggesting their potential as vaccine candidates. In this study, GroEL and OmpX were recombinantly expressed in Escherichia coli and purified as immunogens to immunize pregnant rats. Three days after birth, the progeny were challenged with C. sakazakii to determine the protective effect of maternal immunity on the offspring. The results showed that immunization during pregnancy decreased bacterial load in the brain and blood, reduced brain and intestine damage, and significantly increased specific antibody titers in the offspring. Immunization with the recombinant proteins significantly increased cytokine levels in the serum of the progeny. The group whose mothers were immunized with OmpX produced more IL-4, while the group whose mothers were immunized with GroEL produced more IFN-γ, suggesting that the immunogens enhanced the Th2 and Th1 responses, respectively. However, although the immune response was induced by both proteins, only the offspring of the pregnant rats immunized with OmpX or OmpX/GroEL mixture showed delayed death, possibly because immunization with OmpX led to a stronger humoral immune response in the offspring, suggesting that OmpX was a better vaccine candidate than GroEL. This study first indicated that exposure to C. sakazakii proteins during pregnancy could improve the offspring’s ability to resist infection caused by this pathogen.